Avaliação dos impactos de um programa de mobilidade acadêmica internacional: o caso Brasil-França, ao nível de graduação em ciências agrárias - Goes, Marcos Linhares (2016)
The internationalization of higher education refers to the increasing interconnections among national education systems, in which the sending and receiving of students, professors and technical-administrative staff is an essential component. In this context, the present study aims at assessing the international academic mobility program CAPES-BRAFAGRI, from 2006 to 2014, contained in the public policy of internationalization of higher education Binational University Partnerships. The study takes as starting point regulatory documents from CAPES and from UFG and processes mapping that describe the actions of BRAFAGRI program: funding, eligible undergraduate courses, selection, sending and receiving of students and evaluation of the activities performed. To measure the academic performance during the mobility period, were collected data on the studied subjects, approved and utilized in academic processes and, to measure the students perceptions on international academic mobility and employability trend, was submitted to them a structured questionnaire. Through documents and mapping processes it was described the public policy cycle of the program in which were identified: the actors, the activities, the arenas and the institutional environment. Academic processes information have showed that the number of vacancies offered for academic mobility in French institutions is larger than the demand; students have been approved in 70% of subjects taken, however, only 50% of these disciplines are utilized in specific core of the curriculum structures from original courses; Engineering Food is most likely to celebrate double University Degree. Data on students perceptions have shown: international academic mobility was very important for University Graduation and then employability; the expectation of mobility has been satisfied; language teaching and interculturalism are better in French higher education institutions; few previous foreign languages knowledge hindered the implementation of academic and social integration activities. The internationalization policy of higher education directed to undergraduate students fills a gap by providing to Brazilian students, including low-income, take courses and perform stages in different countries, which contributed to the improvement of student graduation and increased internationalization of Brazilian universities. Studies to adopt the methodology developed in this work can be done in other programs that make up the policy of Capes Binational University Partnerships. As a contribution to the understanding of internationalization of higher education, we suggest further studies on the strategic positioning of the internationalization of higher education in the strategic plans of universities, comparative studies of strategies and outcomes among internationalization of policies made in Brazil and in other countries.